A methods engineering study on EC Lazaro Trading Incorporated - Esquivias, Eugene Ross S.; Gomez, Mirella Giselle M.; Nicolas, Julius D. (Diliman, Quezon City College of Engineering, 2003)
EC Lazaro Trading Inc. (ECL) is one of the leading distributors and producers of flavored lambanog. This paper was made to meet the requirements in IE 32 : Methods Engineering course. Likewise, it was primarily completed so that the study proponents may help in identifying, analyzing, and solving problem areas in ECL's production facility in Pasig. Production efficiency was significanty increased primarily because of the establishment of standards coupled with the optimization of the production line (line balancing). Costs were minimized by the rearrangement of the elements in the production facility by minimizing the relative distances between the said elements. Alternatives were formulated in order to solve the root causes of the major problems. Problem analysis tools taken from methods engineering aided the group in identifying the key areas of concern. The Streamline Diagnosis Diagram and the Ishikawa diagram determined the main problem, causing the delay in production and specified the root causes and their corresponding effects. The root problems identified included the following : the slow return of receivables; unclear Standard Operating Procedures (SOPs) and no established Standard Operating Times (SOTs); the plant layout is not optimal; and low efficiency of the current production methods. Solutions were discussed and possible alternatives were then recommended for each root problem. In the problem of return of receivables, cash flow imbalance may be addressed by : requesting for longer payment terms with suppliers, looking for other suppliers who can give a lower cost of raw materials, and to request for down payments for goods delivered. Work measurements provided the needed data to establish SOPs and SOTs. The efficiency of the production facility will increase by 52.26 percent after using the standard methods and applying the correct procedures. Muther's Strategic Layout Planning (SLP) technique determined the optimal arrangement of the production facility. From the three proposed layouts, the 2nd layout (Figure M.3 Appendix M) saved costs by 27.42 pesos per day. The proposed solutions will increase the profitability of the company by increasing production and lowering the associated costs.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: EC Lazaro Trading Incorporated; Alcoholic beverage industry; Systems analysis